Multi-objective optimization of the heating oil circuit inside the calendering roller for the lithium battery pole piece - Shuangqiu Sun; Junqiang Wang; Rongying Zhang; Zhenchao Si; Zhijie Yang (Scientific Reports)
Abstract The heating oil circuit plays an essential role in the heating calendering roller for the lithium battery pole piece. To achieve the optimization of the heating oil circuit, a fluid-thermal-structural coupling method and a multi-objective optimization procedure are proposed to obtain the optimal solution. A fluid–thermal–structural coupling flowchart based on the numerical modeling for the calendering roller temperature distribution is created to automate the analysis processes in the optimization iteration. In the multi-objective optimization procedure, an integrated optimization framework is established by the prebuilt CAD module and the FEM module in the commercial software. Then, the improved NSGA-II algorithm is selected to execute the optimization loop. The methodology was successfully implemented in a redesigned case of a lithium battery rolling equipment company in China. After redesigning the heating oil circuit inside a calendering roller, both the maximum surface temperature non-uniformity and the maximum surface radial thermal deformation of the roller are reduced remarkably by 29.8% and 13.2%, respectively. The results indicate that the proposed method is feasible and makes designing the heating oil circuit easier. The case illustrates that this method can be extended to practical cases of heating oil circuit design for the lithium battery calendering roller.